FASTKUL: Aplikasi Penyedia Layanan Jasa Tukang Bangunan - Hidayat, Rachmat; Rahardjo, Parsumo; Yudantoro, Tri Rahardjo (JTET (Jurnal Teknik Elektro Terapan), 2017)
Skilled builders known only around the necessary applications to help service the building handyman services to make it easier to get a job and easier for people who want to renovate or build a house. This application is built to benefit society and the craftsman. The purpose of this research Â is to build Fast Kul as application services Android-based builder. The method used in this study is the waterfall methodology, where each step in the methodology of research carried out in sequence, starting from stages of Analysis, Design, Code, Test, and Maintenance. This application uses Adobe Illustrator, AirDroid, Android Studio and Sublime Text. With the "FastKul" is expected to assist users in finding a builder services online and easily. The results of this study can be concluded that the application gets a percentage value of 80.7%, so it can be stated that the application is satisfactory so this application as expected and can be used as needed.Keywords: android, service builder, service providersÂ